The effect of U.S. investor sentiment on cross-listed securities returns: A high-frequency approach - Juan Pablo Gutierrez Pineda; Daniel Perez Liston (Journal of Risk and Financial Management, 2021)
This paper studies the impact of a high-frequency investor sentiment measure (New FEARS) on the returns of foreign securities listed in U.S. markets as American Depository Receipts (ADRs). We recreate a high-frequency investor sentiment measure by aggregating search volume indices (SVIs) for a set of negative economic search terms. We find that ADR aggregate market returns exhibit a negative reaction to increases in searches for negative economic terms such as 'recession', 'crisis', and 'bankruptcy' by U.S. households. This is the first paper to measure the effects of high-frequency investor sentiment on cross-listed securities. Moreover, the results are consistent throughout our study regardless of the variation of sentiment and aggregate market return measure we use. We also explore ADR regional market indices and show that Latin American ADRs are more sensitive to this investor sentiment measure.
Keywords: 330; american depositary receipts; investor sentiment; search volume index